The relations that involve the state, the social classes and the public school under the age of neoliberal capitalism - Clarice Zientarski; Heulalia Charalo Rafante (Universidade Federal de Santa Catarina, 2019)
The paper presents a discussion about the relations that involve the State, social classes and the public school in Brazil, in the context dominated by the neoliberal capitalism. It highlights the main political, economic and social characteristics of this conjuncture, and then deals with the policies directed to the public school, focusing on Basic Education, High School Reform and the Law Project of "Escola sem Partido" (School without Party), showing the convergence of Principles, aiming at maintaining neoliberal hegemony. It is a bibliographical study, based on thinkers who seek to understand and analyze the State articulated to social, political, economic and educational relations, understanding it as a fundamental dimension of the capitalist mode of production, which expresses the relations and antagonisms of classes. Part of the assumption is that, in capitalist society, the political support of the state seeks to complement the capital system, creating conditions for its maintenance and reproduction. This is justified, as in order to continue with its expansion, driven by accumulation, capital presupposes the subordination of society to its objectives, in productive, distributive and reproductive functions. It concludes that the Reform of the Secondary School and the Law of "Escola sem Partido" (School without Party) compose some of the actions of the State in its objective to maintain the contradictions of the existing social classes, favoring the bourgeois order in the domination of the working class, that has in the public school and, especially in Basic Education, often the only space of access to culture and knowledge accumulated historically by humanity, specifically restricting their right to education.